Trust in healthcare and perceived discrimination in Sweden: a fixed effects analysis of individual heterogeneity and discriminatory accuracy - Wemrell, Maria; Hassan, Mariam; Perez-Vicente, Raquel; Lindström, Martin; Öberg, Johan; Merlo, Juan (Frontiers in Public Health, 2025)
IntroductionTrust in healthcare is central to the delivery of care and unequally distributed between groups in society. Experiences of perceived discrimination have been associated with lack of such trust. Although the importance of trust in healthcare has been highlighted in recent years, studies in this area are relatively scarce.Materials and methodsWe investigated the risk of low trust in healthcare in Sweden, using data from 11 consecutive National Public Health Surveys conducted in 2004–2014 (n = 83,135). Applying an analysis of individual heterogeneity and discriminatory accuracy (AIHDA), we investigated the risk of low trust in healthcare across intersectional strata defined by experiences of perceived discrimination as well as sex/gender, educational level, migration status and age. We calculated strata-specific prevalences and prevalence ratios (PR) with 95% confidence intervals (CI). The area under the receiver operating characteristic curve (AUC) was computed to evaluate the discriminatory accuracy (DA) of the intersectional strata.ResultsThe overall prevalence of low trust in healthcare was 25.9%. While low trust was more common among individuals born abroad, with low education and of younger age, discrimination increased the risk of low trust in healthcare over and above the sociodemographic characteristics. The strata with the highest risk of low trust were foreign-born men aged 55–64 years with low income who had experienced discrimination (PR 3.13 [95% CI 2.49–3.95]) and foreign-born women aged 25–34 years with high education who had experienced discrimination (PR 3.05 [95% CI 2.50–3.73]). The DA of the intersectional strata was small (AUC = 0.64), indicating large overlaps between and heterogeneities within strata.ConclusionAs experiences of discrimination, in healthcare and elsewhere, are associated with lack of trust in healthcare, it is incumbent on healthcare professionals to maintain trustworthiness by mitigating discriminatory practices including through striving toward patient-centered communication and care. Such efforts should be universal, although proportionally tailored to mitigate discrimination against patients with a migration background.